Numerical investigation on baffle configuration improvement of the heat exchanger with helical baffles. (1st January 2015) - Jian, Wen; Huizhu, Yang; Wang, Simin; Xu, Shifeng; Yulan, Xue; Tuo, Hanfei
Highlights: Fluid flow and heat transfer was numerically investigated in STHXsHB. Ladder-type fold baffle was proposed to block triangle leakage zones. The shell-side tangential velocity and radial velocity increase significantly. The optimum configuration of ladder-type fold baffle was obtained. The comprehensive performance of the improved heat exchanger is enhanced. Abstract: An improved structure of ladder-type fold baffle is proposed to block the triangular leakage zones in original heat exchangers with helical baffles. The numerical results showed that the shell-side tangential velocity and radial velocity in improved heat exchanger increase significantly and the shell-side fluid becomes approximately continuous spiral flow. And the configuration of ladder-type fold baffles was optimized. The numerical results showed that the shell-side heat transfer coefficient of the improved heat exchanger increases by 82.8–86.1%, when the folding ratio φ is 0.3, the baffle height ω is 60%, and the folding angle α is 37°. The associated pumping power penalty is about 21–549 W due to the increased shell-side pressure drop. The thermal performance factor TEF enhances by 28.4–30.7%, which demonstrates that the ladder-type fold baffle effectively improves the heat transfer performance of heat exchangers with helical baffles. The results of this paper are of great significance in the optimal design of heat exchanger.